Asphalt mix design Using Matlab Computer Program - Al-Hdabi, Abbas; Al-Nasire, Jaafar M; Mohsin, Nadia A (IOP conference series. Materials Science and Engineering, 2020)
An accurate asphalt mix design is a big issue to produce high quality pavement layer. Introduce a computer program that can be used to design different types of asphalt concrete layers i.e. base, binder and surface course will be very helpful. Therefore, the authors are introducing Asphalt Mix Design by MATLAB Program (AMDMAP) software to be used as a replacement to the manual calculations. The input data such as the characteristics of the used materials and lab work results must be available to run this program. The main output will be indicating the optimum asphalt content. Also, the relationships between Marshall Stability, Marshall flow, mixture density, Air Voids, Voids in Mineral Aggregate and Voids Filled with Asphalt vs different contents of asphalt will be produced. Mixture properties at optimum asphalt content will be indicated. Furthermore, the results will be compared with the standard specification of roads in Iraq.